2013
DOI: 10.1108/02621711311318319
|View full text |Cite
|
Sign up to set email alerts
|

The role of coachee characteristics in executive coaching for effective sustainability

Abstract: Purpose -Executive coaching is gaining in popularity as a management developmental activity which facilitates organisational change for sustainability. The purpose of this paper is to explore the relationships among coachee feedback receptivity, pre-training motivation, learning goal orientation, developmental self-efficacy, self-reported job performance improvement, self-awareness, task performance and affective commitment in terms of executive coaching effectiveness as a form of management development. Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 48 publications
2
78
0
Order By: Relevance
“…The review found some limited evidence that coachee motivation expressed through amount of effort invested and an open attitude to change (Audet & Couteret, 2012) in the coaching and self-efficacy are important characteristics linked to positive coaching outcomes (Anderson, 2013;Baron & Morin, 2010;Berg & Karlsen, 2012;Blackman, 2006;Bozer, Sarros, & Santora, 2013;De Haan, Duckworth, Birch, & Jones, 2013;Levy et al, 2002). It is important to note that most, but not all, of the coachees in the 111 studies reviewed were high achievers and/or took on the coaching voluntarily, suggesting little variation in motivation and confidence was available to be examined limiting conclusions.…”
Section: Characteristics Of the Coacheementioning
confidence: 99%
“…The review found some limited evidence that coachee motivation expressed through amount of effort invested and an open attitude to change (Audet & Couteret, 2012) in the coaching and self-efficacy are important characteristics linked to positive coaching outcomes (Anderson, 2013;Baron & Morin, 2010;Berg & Karlsen, 2012;Blackman, 2006;Bozer, Sarros, & Santora, 2013;De Haan, Duckworth, Birch, & Jones, 2013;Levy et al, 2002). It is important to note that most, but not all, of the coachees in the 111 studies reviewed were high achievers and/or took on the coaching voluntarily, suggesting little variation in motivation and confidence was available to be examined limiting conclusions.…”
Section: Characteristics Of the Coacheementioning
confidence: 99%
“…General definitions of coaching, definitions of executive coaching and definitions of coaching in different business contexts were taken for analysis. The articles (Bozer et al 2013;Moen and Federici 2012;Passmore and Fillery-Travis 2011;Stober 2008) were chosen from the academic peer-reviewed journals including: Coaching: An International Journal of Theory, Research and Practice, Journal of Management Development. In addition, books on coaching (Cox et al 2011;Cox 2013; Hamlin et al (2008) for their study into 'conceptualizations and definitions of coaching'.…”
Section: Methodsmentioning
confidence: 99%
“…The results of Baron and Morin (2010) study suggest that coaching can have a real practical impact on the development of strong self-efficacy that enables to perform tasks more effectively. As a management developmental activity, coaching promotes organisational change and leads to sustainability (Bozer et al 2013). As an interactive form of organisational learning and leadership development (De Haan et al 2011, Page andde Haan 2014), coaching enhances the executive's behavioral change through self-awareness and learning, and thereby contributes to individual and organizational success (Bozer et al 2013, Berg & Karlsen 2011.…”
Section: The Nature Of Coaching: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations